Natural and long-lasting cellular immune responses against influenza in the M2e-immune host - Schotsaert, M. (2013)
Influenza is a global health concern. Licensed influenza vaccines induce strain-specific virus-neutralizing antibodies but hamper the induction of possibly cross-protective T-cell responses upon subsequent infection. 1 In this study, we compared protection induced by a vaccine based on the conserved extracellular domain of matrix 2 protein (M2e) with that of a conventional whole inactivated virus (WIV) vaccine using single as well as consecutive homo- and heterosubtypic challenges. Both vaccines protected against a primary homologous (with respect to hemagglutinin and neuraminidase in WIV) challenge. Functional T-cell responses were induced after primary challenge of M2e-immune mice but were absent in WIV-vaccinated mice. M2e-immune mice displayed limited inducible bronchus-associated lymphoid tissue, which was absent in WIV-immune animals. Importantly, M2e- but not WIV-immune mice were protected from a primary as well as a secondary, severe heterosubtypic challenge, including challenge with pandemic H1N1 2009 virus. Our findings advocate the use of infection-permissive influenza vaccines, such as those based on M2e, in immunologically naive individuals. The combined immune response induced by M2e-vaccine and by clinically controlled influenza virus replication results in strong and broad protection against pandemic influenza. We conclude that the challenge of the M2e-immune host induces strong and broadly reactive immunity against influenza virus infection.